2016
DOI: 10.1016/j.fertnstert.2016.07.1115
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline for contraceptive development

Abstract: The high rates of unplanned pregnancy reflect unmet need for effective contraceptive methods for women, especially for individuals with health risks such as obesity, diabetes, hypertension, and other conditions that may contraindicate use of an estrogen-containing product. Improvements in safety, user convenience, acceptability and availability of products remain important goals of the contraceptive development program. Another important goal is to minimize the impact of the products on the environment. Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 79 publications
(81 reference statements)
0
7
0
2
Order By: Relevance
“…4 Some of the new options under development include hormonal and nonhormonal male contraceptive methods, which would give men more options to control their own fertility and increase protection against unintended pregnancy if both partners are using a method. 56 Currently, the majority of women wanting to avoid a pregnancy are using female-controlled modern contraceptive methods, and only 17% are using a method that requires their partner's involvement (male condoms, male sterilization or fertility awareness-based methods). 45…”
Section: Understanding and Addressing Unmet Needmentioning
confidence: 99%
“…4 Some of the new options under development include hormonal and nonhormonal male contraceptive methods, which would give men more options to control their own fertility and increase protection against unintended pregnancy if both partners are using a method. 56 Currently, the majority of women wanting to avoid a pregnancy are using female-controlled modern contraceptive methods, and only 17% are using a method that requires their partner's involvement (male condoms, male sterilization or fertility awareness-based methods). 45…”
Section: Understanding and Addressing Unmet Needmentioning
confidence: 99%
“…Protein antibodi atau molekul kecil lainnya digunakan sebagai agen kontraseptif dalam penurunan produksi dan/atau fungsi sperma pada hewan coba maupun manusia. 10 Kontrasepsi Pria dengan Target Molekul pada Sel Gamet Beberapa sel memiliki permukaaan antigen yang unik, salah satunya adalah sel gamet (sperma) yang bersifat imunogenik, spesifik, dan dapat dikenali oleh antibodi. Sperma memiliki sifat yang unik yaitu bersifat autoantigen dan isoantigen sehingga mampu memicu produksi antibodi pada tubuh.…”
Section: Metodologiunclassified
“…In 2016, 1 324 518 prescriptions of SARCs were collected, compared to 113 986 prescriptions of LARCs (106). IUDs are the most cost-effective methods (107) and are also the most eco-friendly in terms of environmental impact (108). These arguments, together with the fact that several studies have shown that LARC promotion leads to a reduction of unintended pregnancies and repeat abortions (22,109) should appeal to Swedish stakeholders and contraceptive users.…”
Section: Contraceptive Counsellingmentioning
confidence: 99%